PENGARUH PEMBELAJARAN KONTEKSTUAL DENGAN TEKNIK HANDS ON MATHEMATICS TERHADAP KEMAMPUANKOMUNIKASI MATEMATIK SISWA KELAS IX MTS DARUSSALAM KABUPATEN PESISIR SELATAN - Meria Ultra Gusteti; Sefrinal Sefrinal; Okviani Syafti (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2018)
This research began from issues of the low Mathematicabilities students of class IXMTsDarussalam.This research is aimed to reveal the effect of Cooperatif modelswith Hands On Mathematic in mathematicstudents ability started from high, averageand lowof students in influencing early understanding concept ability. This research is a quasi experimental design. The population in this research is all students of class IXMTsN Darussalam Selasa. The sampling technique used is Random Sampling. Samples of this research are the students of class IX.1 as the experimental class and class IX.3 as the control class. The instrument used is a test consists of beginning capabilities test and posttest to see the comunicationmathematicability. Data analysis was performed using t-test.There are some conclusions that can be acquired based on the results of research and discussion. First, the students which use contextuallearning type with hands on mathematics technic have higher comunicationmathematic abilitythan students that use the conventional learning. Second, the high,average and low starting students ability which use contextuallearning type with hands on mathematics technic have highercommunication mathematic ability than students that use the conventional learning.